Flipping the Script of "Official Knowledge" Through Multimodal Composition. (3rd April 2022) - Billen, Monica T.; Ward, Natalia A.; DeHart, Jason D.; Moran, Renee R.; Yang, Shuling
Abstract: Even in online and distance formats, multimodal composition can be a means of sustaining culture and engaging children. The Teach Us project combines multimodal composition, family cultural resources, and student voice.